The Citrus Variety Improvement Program in Spain - Navarro, Luis (iocv, 2022)
Virus and viruslike diseases are the most serious threats facing the Spanish citrus industry today. Tristeza in 1972 affected 82,000 hectares of citrus (Guardiola, 1974), and is now the most dangerous citrus disease in Spain. Because of tristeza, sour orange can no longer be recommended as a rootstock and such tristeza tolerant stocks as citranges and Cleopatra mandarin are being substituted. However, since nearly all trees in Spain may have exocortis (Planes et al., 1968) the use of citranges may lead to another serious problem because of their susceptibility to exocortis. Xyloporosis (cachexia) is widely distributed in Spain (Planes et al., 1973) and its presence may diminish the effectiveness of Cleopatra mandarin as a rootstock. Psorosis and psorosis-related viruses are present in much of our citrus and presumably add to decline and stunting of trees, thereby increasing economic loss. Similarly, impietratura is present in several varieties and is an important factor in diminishing.